RATIONAL USAGE OF DEPOSITS DURING THE GAS (GAS CONDENSATE) FIELDS DEVELOPMENT: THE ISSUES OF LEGAL PROVISION - R. N. Saliyeva (Russian Journal of Economics and Law)
In accordance with legislation on natural deposits the author gives an account of the main requirements for the deposits' rational usage and protection. The author states that the provision of the established requirements should be supported by the technical legislation norms. On the basis of the existing norms in the regulation sphere, in particular, for such processes as projecting of the construction of gas and gas condensate deposits, the author determines the specifics of the legal provision of the deposits rational usage during the productive activity. The objectives of legal provision of the deposits' rational usage are set; the suggestions for legislation improvement are made.